Electricity Supply, Fossil fuel Consumption, Co2 Emissions and Economic Growth: Implications and Policy Options for Sustainable Development in Nigeria. - Nnaji, Chibueze Eze; Chukwu, Jude O.; Nnaji, Moses (International Journal of Energy Economics and Policy, 2013)
<!--[if gte mso 9]> 800x600 <![endif]--> This paper investigates the causal relationship among electricity supply, fossil fuel consumption, CO2 emissions and economic growth in Nigeria for the period 1971-2009, in a multivariate framework.Using the bound test approach to cointegration, we found a short-run as well as a long-run relationship among the variables with a positive and statistically significant relationship between CO2 emissions and fossil fuel consumption. The findings also indicate that economic growth is associated with increased CO2 emissions while a positive relationship exists between electricity supply and CO2 emissions revealing the poor nature of electricity supply in Nigeria. Further, the Granger causality test results indicate that electricity supply has not impacted significantly on economic growth in Nigeria. The results also strongly imply that policies aimed at reducing carbon emissions in Nigeria will not impede economic growth. The paper therefore concludes that a holistic energy planning and investment in energy infrastructure is needed to drive economic growth. In the long-run however, it is possible to meet the energy needs of the country, ensure sustainable development and at the same time reduce CO2 emissions by developing alternatives to fossil fuel consumption, the main source of CO2 emissions. Keywords: CO2 emissions; Economic growth; Electricity supply; Granger causality; Bounds testing; Fossil fuel consumption. JEL Classification: Q41; Q42; Q43 <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} --> <!--[endif] -->